HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEPATUHAN DIET DM PADA PASIEN DIABETES MELLITUS - Herlambang, Tri Mulyono; Anasril, Anasril (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Diet therapy is very important for people with diabetes mellitus, because by undergoing the right diet therapy, blood glucose levels and weight can remain normal. For people with DM, knowledge and attitudes about sugar diets, including the type, amount, and schedule, are the first steps in forming healthy behaviors in controlling blood sugar. This study aims to determine the relationship between knowledge and attitudes with adherence to a sugar diet in people with diabetes mellitus. The type of research used in this study is quantitative, with a cross-sectional study design. Data collection techniques used questionnaires. There were 35 respondents in this study. Data analysis used the Chi-Square test. The results of the study showed that there was a significant relationship between knowledge and attitude with diet compliance with a p-value of 0.012 (p<0.05) and p=0.004 (p<0.05). It is recommended that the Sawang Community Health Center provide education on diet compliance and good eating habits to people with diabetes mellitus.